Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Sepatu Futsal Pada Topscore Depok - Nurul Choirunnisa; Rani Kurniasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to test and analyze the effect of product quality and service quality on the decision to purchase futsal shoes on the Depok Topscore. The technique for determining the number of samples taken as respondents in this study was by using the Slovin formula, so it can be seen that the sample of this study was 85 respondents. The sampling method used in this study was a random sample method and data collection techniques by distributing questionnaires. Data processing in this study uses the IBM SPSS version 25 program to calculate the validity test and reliability test, classical assumption test, multiple regression test and hypothesis test. The test results show that product quality and service quality have a positive and significant impact on consumer purchasing decisions for futsal shoes on the Depok Topscore..